Comparison of Four Methods for Corneal Thickness Measurement - Teodora Marinova; Vesela Ivancheva; Svilena Peeva; Christina Grupcheva (Journal of Biomedical & Clinical Research)
The aim of the study was to evaluate the thickness of the normal cornea in order to establish correlation between four methods of measuring including: ultrasound pachymetry (USP), anterior segment optical coherence tomography (ASOCT), non-contact tono/pachymetry (TONOPACHY) and laser-scanning confocal microscopy (LSCM). The study was based on evaluating repeatability and comparability of four different methods formeasuring the corneal thickness. Non contact specular microscopy was first performed on all 27 patients (aged between 20 and 24 years) to evaluate corneal characteristics and confirm the absence of pathological changes. Each participant was examined by USP, ASOCT and TONOPACHY, and 13 eyes of 10 persons were also examined by LSCM. The values of average central corneal thickness measured by USP, ASOCT, TONOPACHY and LSCM were 532.20±4.5 pm, 553.33±12.1 pm, were 548.20±5.62 pm and 573.33±7.22 pm, respectively. There was a high correlation between the instruments. The mean differences for central corneal thickness measurements were 41.43±1.67 pm between USP and LSCM, 20.43±2.4 pm between USP and ASOCT, and 22.1 ±3.88 pm between USB and TONOPACHY. Anterior segment optical coherence tomography overestimated corneal thickness as compared with that measured by USP, which is believed to be a gold standard. Anterior segment optical coherence tomography had better agreement with USP, as compared with LSCM. However, the results of measured cornea thickness by TONOPACHY were very close to cornea thickness measured by ASOCT.